Annual Mammographic Screening Reduces the Risk of Interval or Higher Stage Invasive Breast Cancers Among Postmenopausal Women in the Ontario Breast Screening Program. Issue 3 (August 2022) - Blackmore, Kristina M; Chiarelli, Anna M; Mirea, Lucia; Mittmann, Nicole; Muradali, Derek; Rabeneck, Linda; Done, Susan J
Purpose: In the Ontario Breast Screening Program (OBSP) annual screening improved breast cancer detection for women 50–74 years with a family/personal history compared to biennial, while detection was equivalent for women screened annually for mammographic density ≥75%. This study compares the risk of interval or higher stage invasive cancers among postmenopausal women screened annually vs biennially by age and estrogen use.Methods: A retrospective design identified 4247 invasive breast cancers diagnosed among concurrent cohorts of women 50–74 screened in the OBSP with digital mammography between 2011 and 2014, followed until 2016. Polytomous logistic regression estimated the risk of interval or higher stage breast cancers by age and estrogen use between women screened annually because of first-degree relative with breast or ovarian cancer or personal history of ovarian cancer, or mammographic density ≥75%, and those screened biennially.Results: The risk of interval vs screen-detected cancers was significantly reduced in women screened annually for family/personal history (OR=.64; 95%CI:0.51–.80), particularly those 60–74 years (OR=.59; 95%CI:0.45–.77) or not currently using estrogen (OR=.66; 95%CI:0.52–.83) compared to those screened biennially. The risk of stage II–IV vs stage I tumors was also lower in women 60–74 years screened annually for family/personal history (OR=.79; 95%CI:0.64–.97) and in those screened annually for mammographic density ≥75% currently using estrogen (OR=.51; 95%CI:0.26–1.01) compared to women screened biennially.Conclusion: Postmenopausal women at increased risk screened annually had equivalent or reduced risks of interval or higher stage invasive breast cancers than those screened biennially, further supporting risk-based screening in this population.